A study of Î”IAQHKH,Study of Covenant - Bird, Ian Keith (Rhodes University, Faculty of Divinity, Department of Divinity, 1965)
From Preface: The Church has been divided from its very earliest days, when Christians of Jewish origin found it hard to accept that uncircumcised Gentiles might be Christians too. (See Acts 15, Galatians 2, etc.) It has since then known division into East and West, into Roman Catholic and Protestant, and into the hundreds and even thousands of denominations and sects which we know today, not to speak of the schisms between 'modernism' and 'fundamentalism', between Calvinism and Arminianism, and between 'High' and 'Low' churchmanship. We are, however, being reminded more and more by the Ecumenical Movement that the Church of Christ is ONE. Jesus said: "On this rock I will build my Church" (not churches) - Matt. 16:18.
Keywords: Covenant theology; Covenants -- Religious aspects -- Judaism